Evaluation of stochastic oscillator and parabolic sar technical indicator performance in investment strategy decision-making - Detri Heri Gemita; Asri Usman; Mediaty; Nur Huzaemah (E-Jurnal Akuntansi, 2025)
The capital market plays an important role in the economy, with stocks as the main investment instrument that has the potential for high returns as well as fluctuating risks. To reduce risk, technical analysis is used through leading and lagging indicators to predict price direction. This study aims to compare the performance of the Stochastic Oscillator as a leading indicator and the Parabolic SAR as a lagging indicator in supporting stock investment decisions. The research method uses a descriptive and comparative quantitative approach with daily stock price data from the IDXGrowth30 index for the 2024 period. The analysis includes accuracy, profitability, and risk, which are tested using a t-test and Welch's t-test. The results show that the Stochastic Oscillator has an accuracy of 78.12%, a cumulative return of 1,112.10%, and a risk of -17.27%, while the Parabolic SAR has an accuracy of 30.56%, a cumulative return of -100%, and a risk of -5,332.09%. The conclusion shows that the Stochastic Oscillator is statistically and empirically superior in generating accurate signals, high profits, and lower risk.